Minimal self-consciousness and the flying man argument - Gallagher, Shaun (Frontiers in Psychology, 2023)
The concept of minimal self-consciousness or “minimal self” is equivalent to a very basic form of first-person, pre-reflective self-awareness, which includes bodily self-awareness, and is related to phenomenal experience (qualia) and sentience. This phenomenological concept plays a role in characterizations of the senses of ownership and agency; in recent debates about Buddhist conceptions of the no-self; in explanations of illusions such as the Rubber Hand Illusion; as well as in characterizations of schizophrenia as a self-disorder. Despite its relevance to these complex investigations, a number of theorists have recently pointed out that the concept is not well defined. In order to provide some clarification about the notion of minimal self and how it relates to bodily and sensory processes this paper reaches back to the ideas expressed in a famous medieval thought experiment proposed in the 11th century: Avicenna’s Flying Man argument. The paper then provides a review of some of the contemporary debates about the minimal self, pointing especially to questions about the role of bodily and social processes.